Conservation of river terrapin (Batagur affinis) in Malaysia: status and challenges - Abdul Rahman, Muhammad Farhan; Abd Manaf, Latifah (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
With the steady declining of nesting river terrapin reported annually in Malaysia, it is just a matter of time before this species listed extinct in IUCN Red List of Endangered Animal. This paper attempts to develop an overview on the current status, conservation effort, and challenges in conservation of river terrapin (Batagur affinis) in Malaysia. Lack of knowledge and lack of enforcement of law and regulation is the two main factors contribute to the failure of conservation of wildlife in Malaysia. Overview on the existing conservation programme at Perak and Kedah show that the programme are not sustain and number of terrapin successfully being breed annually is decreasing. It was relevant to enhance proper approach in the management from wildlife conservation perspective. Despite the high potential and opportunities and successfulness at Terengganu in conserving river terrapin, we should try to replicate the programme in Terengganu to Perak and Kedah as well. The government should committed to significantly improve the facilities in Perak and Kedah to promote and enhance the programme. With issues and challenges in river terrapin conservation that were highlighted in this context especially from the, aspects of knowledge and awareness, availability and other loopholes within policies and, related wildlife conservation such as turtle within the country, the question on whether the goals in increasing the wild population of river terrapin remains unsure of but there is a possibility for a successful implementation of sustainable conservation programme.